2015
DOI: 10.1097/cad.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Biochanin A inhibits endothelial cell functions and proangiogenic pathways

Abstract: Malignant gliomas, such as glioblastoma multiforme, are highly vascularized tumors of the central nervous system. A rich network of angiogenic vessels supporting glioma growth is an important therapeutic target in glioma therapy. In the past few years, small molecules have gained interest as multitargeting therapies for cancer. Biochanin A is a small, natural dietary isoflavone known for its anticancer potential. Previously, we have found that biochanin A inhibits invasion in human glioblastoma cells. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
(54 reference statements)
0
25
0
Order By: Relevance
“…Gliomas are serious primary brain tumors, which account for 80% of malignant tumors of the central nervous system in the United States. Current therapeutic strategies for this type of brain cancer are inadequate and the median survival rate for patients with malignant glioma is 14 months due to their aggressive nature, high recurrence rate, and gradual increase in radiotherapy and chemotherapy resistance ( 1 ). Therefore, it is vital to examine the mechanisms underlying the progression of glioma and to urgently develop novel therapies with improved therapeutic effects for the treatment of patients with glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Gliomas are serious primary brain tumors, which account for 80% of malignant tumors of the central nervous system in the United States. Current therapeutic strategies for this type of brain cancer are inadequate and the median survival rate for patients with malignant glioma is 14 months due to their aggressive nature, high recurrence rate, and gradual increase in radiotherapy and chemotherapy resistance ( 1 ). Therefore, it is vital to examine the mechanisms underlying the progression of glioma and to urgently develop novel therapies with improved therapeutic effects for the treatment of patients with glioma.…”
Section: Introductionmentioning
confidence: 99%
“…() showed significant anti‐cancer efficacy of silibinin and proposed chemical modifications to enable it to impart potent anti‐cancer efficacy; (ii) Biochanin A: Jain et al . () proposed the use of biochanin A in gliomas because it inhibited proangiogenic pathways, vascular endothelial growth factor and chemical hypoxia inducible factor in their preclinical investigation; (iii) Baicalin: In this report, baicalin showed inhibition of both superoxide dismutase (SOD) and hypoxia inducible factor‐1 (HIF‐1), and hence there was a potential to be used in lung carcinoma and lung metastasis where both SOD and HIF‐1 pathways are prevalent (Du et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration that may be important in the selection of the flavonoid could also be the potential effect of the chosen flavonoid to independently demonstrate anti-cancer potential either in a preclinical, in vitro or clinical setting. Examples include: (i) Silibinin: Agarwal et al (2013) showed significant anti-cancer efficacy of silibinin and proposed chemical modifications to enable it to impart potent anti-cancer efficacy; (ii) Biochanin A: Jain et al (2015) proposed the use of biochanin A in gliomas because it inhibited proangiogenic pathways, vascular endothelial growth factor and chemical hypoxia inducible factor in their preclinical investigation; (iii) Baicalin: In this report, baicalin showed inhibition of both superoxide dismutase (SOD) and hypoxia inducible factor-1 (HIF-1), and hence there was a potential to be used in lung carcinoma and lung metastasis where both SOD and HIF-1 pathways are prevalent (Du et al, 2010).…”
Section: Relevance To Anti-cancer Therapymentioning
confidence: 99%
“…In addition, owing to the structural similarities between BCA and estrogen, BCA can exert both estrogenic and anti-estrogenic effects 4 and is marketed for the treatment of inflammation, 5,6 osteoporosis, 7,8 and other diseases. 9,10 However, its clinical efficacy is limited by its low oral bioavailability, which is due to poor water solubility, high clearance, and large apparent volume of distribution. 11 Hence, new delivery systems are required to improve the performance of BCA.…”
Section: Introductionmentioning
confidence: 99%